2023
DOI: 10.1002/adma.202211099
|View full text |Cite
|
Sign up to set email alerts
|

Toward Electrocatalytic Methanol Oxidation Reaction: Longstanding Debates and Emerging Catalysts

Abstract: The study of direct methanol fuel cells (DMFCs) has lasted around 70 years, since the first investigation in the early 1950s. Though enormous effort has been devoted in this field, it is still far from commercialization. The methanol oxidation reaction (MOR), as a semi‐reaction of DMFCs, is the bottleneck reaction that restricts the overall performance of DMFCs. To date, there has been intense debate on the complex six‐electron reaction, but barely any reviews have systematically discussed this topic. To this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
73
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 187 publications
0
73
0
Order By: Relevance
“…These results show that the presence of Pd promotes the complete oxidation of methanol to CO 2 . Figure S12 shows the possible reaction paths of the methanol oxidation reaction . Since no characteristic signal of the CO* intermediate was detected in the infrared spectra of Pt 1 Pd 1 -N NFs/CP and 20 wt % Pt/C, we propose that the MOR follows the CO-free path on both catalysts.…”
Section: Resultsmentioning
confidence: 98%
“…These results show that the presence of Pd promotes the complete oxidation of methanol to CO 2 . Figure S12 shows the possible reaction paths of the methanol oxidation reaction . Since no characteristic signal of the CO* intermediate was detected in the infrared spectra of Pt 1 Pd 1 -N NFs/CP and 20 wt % Pt/C, we propose that the MOR follows the CO-free path on both catalysts.…”
Section: Resultsmentioning
confidence: 98%
“…19,20 In addition, there is intense debate about the exact reaction pathway of MOR on a specific surface due to the complexity of the multiple reaction steps (six electrons gained and loss) and the wide range of intermediates. 9,21 Wang 23 In brief, unified mechanism understanding and proper descriptors are lacking to guide the design of MOR catalysts, which severely hinder the development of DMFC. 24,25 Hence, it is of significant importance to screen non-noble-metal MOR electrocatalysts with high activity and selectivity.…”
mentioning
confidence: 99%
“…In recent years, the rapid growth of energy consumption has stimulated extensive research for renewable energy technologies. The direct methanol fuel cell (DMFC), as one of the most promising fuel cells for portable power equipment and mobile vehicles, , has attracted great attention due to the following advantages: , (1) liquid methanol is easier to transport and less risky to be stored than hydrogen; (2) methanol with a high H/C ratio has a high calorific value (≈22.7 MJ kg –1 ) and a lower calorific value market price as opposed to gasoline; (3) DMFC is a prominent fuel cell technology that produces only carbon dioxide, water, and no sulfur-containing gases. However, to develop low-cost, high-efficiency, and CO-tolerant electrocatalysts of the methanol oxidation reaction (MOR) in the anodic electrode is still a challenge for DMFC. , Moreover, recent reports show that the main high-performance MOR catalysts are noble platinum group metals, such as Pt NPs, Pt 1 RuO 2 , and PtCu, whereas CO poisoning results in the occupation of the active sites and the formation of CO byproducts, which reduces the efficiency and selectivity of Pt-based catalysts. , More importantly, the low abundance and high cost of noble metals limit their wide uses for MOR. , In addition, there is intense debate about the exact reaction pathway of MOR on a specific surface due to the complexity of the multiple reaction steps (six electrons gained and loss) and the wide range of intermediates. , Wang et al have shown the possible MOR reaction path on the surface of nickel hydroxide nanoribbon (NR-Ni(OH) 2 ) to be *CH 3 OH → *CH 3 O → *CH 2 O → *CHO → *CO → *COOH → *CO 2 , in which H 2 O was captured by *CO and then dehydrogenated to generate *COOH . Another case shows that H 2 O was captured by *CH 2 O and dehydrogenated to produce *CH 2 OOH discovered on the surface of ZnCu(111) with the pathway of *CH 3 OH → *CH 3 O → *CH 2 O → *CH 2 OOH → *CH 2 OO → *CO 2 .…”
mentioning
confidence: 99%
“…However, the high cost of these precious metals is a major barrier to large-scale implementation of MOR catalysts for DMFCs. Many transition metal catalysts have been demonstrated to be active toward MOR in alkaline conditions, but MOR onset potentials of these catalysts are too high to be used in DMFCs [5][6][7] . Furthermore, methanol decomposition on transition-metal surfaces generates poisoning adsorbates (especially CO 8 ), which hinder their catalytic activity.…”
mentioning
confidence: 99%
“…Many transition metal catalysts have been demonstrated to be active toward MOR in alkaline conditions, but MOR onset potentials of these catalysts are too high to be used in DMFCs. [5][6][7] Furthermore, methanol decomposition on transition-metal surfaces generates poisoning adsorbates (especially CO 8 ), which hinder their catalytic activity. Therefore, developing transition metal-based catalysts with high MOR activity, stability in acid conditions, and superior CO tolerance is of great significance and importance.…”
mentioning
confidence: 99%